2020
DOI: 10.1111/apps.12257
|View full text |Cite
|
Sign up to set email alerts
|

Two Tales of Rumination and Burnout: Examining the Effects of Boredom and Overload

Abstract: Although boredom poses serious consequences for employees and organizations, research has paid little attention to this phenomenon, especially when compared to other job experiences such as overload. Building upon the Effort‐Recovery Model, our study examines the impact of these two sub‐optimal experiences, characterized by under‐ and over‐stimulation, on burnout via three facets of rumination. Using a time lagged design with three measurement moments and a sample of 152 participants, we found partial support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
(122 reference statements)
1
25
0
2
Order By: Relevance
“…We deemed boredom to be a suitable control condition as it is a negatively valanced affective state that is linked with increased sensation-seeking and rumination (Bench & Lench, 2019; Sousa & Neves, 2020; van Tilburg & Igou, 2017). Further, experiences of boredom and anger last approximately the same amount of time (i.e., two hours; Verduyn & Lavrijsen, 2015).…”
Section: Studymentioning
confidence: 99%
“…We deemed boredom to be a suitable control condition as it is a negatively valanced affective state that is linked with increased sensation-seeking and rumination (Bench & Lench, 2019; Sousa & Neves, 2020; van Tilburg & Igou, 2017). Further, experiences of boredom and anger last approximately the same amount of time (i.e., two hours; Verduyn & Lavrijsen, 2015).…”
Section: Studymentioning
confidence: 99%
“…Boredom is associated with worry in college students (Kelly & Markos, 2001 ), and boredom and worry often co-occur in everyday life (Chin et al, 2017 ). In support of boredom influencing future RNT, one study found that workplace boredom predicted rumination one week later (Sousa & Neves, 2020 ). Indeed, researchers suggest that boredom precedes RNT when they theorize that bored individuals may use RNT to meet their need for stimulation (Kelly & Markos, 2001 ) or may be prone to engage in RNT as they repeatedly ponder a problem while feeling unable to take action (Mugon et al, 2018 ).…”
mentioning
confidence: 99%
“…Monotonous landscape along the way during transportation duty on the plateau makes plateau drivers feel bored. Recent studies found that boredom was associated with burnout [34,35]. Different culture and customs, far away from home, and di culties in contacting with friends and family may cause plateau drivers lack of social support.…”
Section: Discussionmentioning
confidence: 99%